Polymers with Nano-Encapsulated Functional Polymers: Encapsulated Nanoparticles for Treatment of Cancer Cells. Encapsulated Nanoparticles for Treatment of Cancer Cells. - Tebaldi, Marli Luiza; Belardi, Rose Marie; Montoro, Sérgio Roberto [UNESP] (Elsevier, 2015)
In the last decades, the interplay between basic science and technology has triggered remarkable advances in the materials field. Polymer science, which draws on the knowledge of organic and physical chemistry, materials science, engineering and biochemistry, allows researchers to collaborate on the creation of a variety of new polymeric materials for different applications. The search for materials with unique molecular scale properties resulted in a huge industrial impact on diverse areas such as pharmacy, medicine, food industry, biotechnology, cosmetics, biosensor devices, nanocomposite materials, and alternative energy resources. The symbiosis among nanoscience and nanotechnology, biological science and biomedicine is expected to radically improve therapeutic treatments that would be barely possible using conventional strategies. The polymer functionalization and the size reduction from the micrometer to the nanometer range have a significant effect on the surface architecture. This is particularly important for biomaterials because the interaction with proteins and cell surfaces can be improved. This chapter focuses specifically on polymeric nanoparticles (NPs) for the treatment of cancer cells, exploring examples from the literature and discussing some future trends related to this topic.
Keywords: Cancer therapeutics; Functional polymers; Nano-encapsulated drug; Nanoscience; Polymeric blend